Effect of low gamma radiation exposures on rice seedling development - Abifarin, A.O; Rutger, J.N. (1982)
In two of four experiments, low dosage gamma radiation significantly increased height of rice seedlings. In the two experiments in which roots were measured, the number of secondary roots per seedling was increased by an exposure of 0.5 kR applied after the rice seeds had been pre-soaked for 24 hr. However, the stimulatory effects of low exposures of gamma rays on rice seedlings were generally small and do not appear useful in stimulating seedling development.